Reflections on Collective Insecurity and Virtual Resistance in the times of COVID-19 in Malaysia - Lumayag, Linda; Del Rosario, Teresita; Sutton, Frances S. (Migration Letters, 2020)
Environments of human insecurity are a widespread problem in our globalised world, particularly for migrant workers, one of the most vulnerable groups in society today. These experiences of insecurity have been heightened in the context of the COVID-19 pandemic. In this article, we examine the collective experience of insecurity among migrant workers in Malaysia. In our analysis, we outline collective insecurity at two levels: the micro level of migrant workers’ daily, subjective experiences of insecurity; and the macro level, in which insecurity is a consequence of structural forces, specifically the globalisation of labour. These two levels interact symbiotically, producing states of insecurity that are concretely experienced as anxiety and fear. Migrant workers in Malaysia also practice agency through small forms of resistance that they use to bolster one another and reduce their insecure experiences. Throughout the COVID-19 pandemic and subsequent Movement Control Order (MCO) in Malaysia, migrant workers have been further marginalised by the state, but they have also become connected to one another through acts of solidarity and resistance. However, the sustainability of these forms remains unclear.